PENGARUH PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA DI SMK NEGERI 1 KANDIS - Lingga, Putri Ramadani; Kartikowati, Sri; Sumarno, Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the influence of entrepreneurs knowledge to the interest in entrepreneurship of students at SMK Negeri 1 Kandis. The population in this study ware 11th grade students at SMK Negeri 1 Kandis which amounted to 167 students from 4 (four) department. Department of Computer and Network Engineering, Accounting, Office Administration and Light Vehicle Engineering. This study using cencus technique which was all of the populations put into sample. Data was collected using tests for entrepreneurial knowledge while questionnaires for interest in student entrepreneurship. Data then was analyzed using simple linear regression test. The result showed that entrepreneurs knowledge had a significant effect on interest in entrepreneurship of students at SMK Negeri 1 Kandis. Entrepeneurship knowledge variable had a contribution amounted 0.667 or 66.7% while the remaining amount of 33.3% is explained by other factors which was not examined in this study.Key Words: Knowledge of entrepreneurship, Interest in entrepreneurship